Essential oils as a good weapon against drug-resistant Candida auris - Fernandes, Liliana Sousa (2022)
Candida auris is a recently found Candida species, mainly associated with nosocomial outbreaks in intensive care hospital settings, and unlike other Candida species, it can be transmitted through person-to-person or by contact with surfaces. C. auris is described as resistant to first-line antifungals and, consequently, associated with high mortality. Nowadays, essential oils (EOs) are known to be effective against fungal and bacterial infections. This work aimed to evaluate the effect of four EOs (tea tree, niaouli, white thyme and cajeput) against C. auris. The EO’s effect on C. auris planktonic growth was evaluated by the minimum inhibitory concentration determination and by the agar disc diffusion method. Then, the same effect was evaluated on biofilm by colony-forming units’ enumeration. The results showed that EOs were able to inhibit the C. auris planktonic growth, with an MIC50 between 0.78 and 1.56% and halos of 20–21 mm for white thyme and tea tree and 13–14 mm for cajeput and niaouli. In addition, the EOs were also able to completely inhibit biofilm formation. Moreover, white thyme and cajeput completely eradicate pre-formed biofilms, while tea tree and niaouli significantly reduce it. Thus, this work demonstrates that EOs are a possible therapeutic alternative and a future perspective for the hard fight against C. auris.